Lower Socio-economic Status and Cardiovascular Disease: Role of Healthcare Facility and Policy in India - Singh, Arti; Dixit, Shikha (Indian Journal of Community Health, 2016)
Background: Cardio-vascular disease (CVD) is one of the main cause of mortality Worldwide and India is no exception. Unlike developed countries, where both CVD prevalence and mortality has been established to affect lower socio-economic status (SES), in India there is no consensus among researchers over socio-economic patterning of CVD prevalence but the mortality rate has been reported to disproportionately affect the economically weaker sections. Aims & Objectives: This article, focuses at the issue of how lack of good healthcare facilities and non-supportive health policies are affecting CVD mortality positively among lower SES of India. Challenges of the Indian healthcare system in context of lower SES can be described in terms of the issue of availability, accessibility and affordability. Inadequate policy and public healthcare system either leads to the problem of high Out-of-Pocket Payments (OPP) or opting out of the treatment, which further increases poverty and mortality among them. Moreover, limited insurance coverage and inadequate regulatory policies for alcohol and tobacco-leading CVD risk factors among lower SES groups – do little to discourage its use among them. Conclusion: Since, lower SES people in India are already under the burden of communicable diseases, government should take immediate steps to control the mortality among them by creating a supportive environment through pro-poor health policies and healthcare facilities.